The Virgin Mary in Byzantium, c.400-1000 : hymns, homilies and hagiography - Cunningham, Mary (Lecturer in historical theology and Othodox Christian studies) (Cambridge University Press, 2022)
The Virgin Mary assumed a position of central importance in Byzantium. This major and authoritative study examines her portrayal in liturgical texts during the first six centuries of Byzantine history. Focusing on three main literary genres that celebrated this holy figure, it highlights the ways in which writers adapted their messages for different audiences. Mary is portrayed variously as defender of the imperial city, Constantinople, virginal Mother of God, and ascetic disciple of Christ. Preachers, hymnographers, and hagiographers used rhetoric to enhance Mary's powerful status in Eastern Christian society, depicting her as virgin and mother, warrior and ascetic, human and semi-divine being. Their paradoxical statements were based on the fundamental mystery that Mary embodied: she was the mother of Christ, the Word of God, who provided him with the human nature that he assumed in his incarnation. This title is also available as Open Access on Cambridge Core.